Analysis of Construction Materials of Xiongnu Tongwan City, Built 1600 Years Ago. (3rd October 2021) - Weng, Xin; Zhang, Bingjian; Li, Shaopeng
ABSTRACT: The ruins of Tongwan City, built by the Steppe peoples of Xiongnu, are the most completely preserved Xiongnu ruins in China. In 2012, the site of Tongwan City was included in the preliminary list of world cultural heritage sites in China, and its special status among Chinese city sites was revealed. In order to understand the construction materials and processes of the Xiongnu city from 1600 years ago, this study sampled and comprehensively detected the wall materials of Tongwan City's west city. The investigation included analyses of mineral composition, carbonate content, sand and clay particle size, and organic additives and cementing agents. By making simulated samples, we explored the factors that affected the appearance of color in the rammed earth. The test results show that the main material of Tongwan City's city walls is tabia, which is a common Chinese building material composed of lime, sand, and clay. Chemical analysis showed that the wall material generally contained protein components, and further detection by immunoassay revealed that it contained peach gums. Through the production of simulated sample blocks and color analysis, we found that the wall's whiteness is probably due to a combination of factors. These include an overall higher proportion of lime content, the use of lighter river sediment clay, higher temperature maintenance, and calcium carbonate on the surface of the city wall.